Agresi verbal di media sosial pada remaja penggemar K-Pop: Bagaimana peranan fanatisme? - Syara Farkhana Febriany; Dyan Evita Santi; Aliffia Ananta (INNER: Journal of Psychological Research, 2022)
This study aims to examine whether there is a relationship between fanaticism and verbal aggression in adolescents. The participants of this study were 134 adolescents who were taken using a simple random sampling technique, the participants consisted of 78 boys and 56 girls. The research instrument used a fanaticism scale and a verbal aggressiveness scale. Based on the results of data analysis using the product-moment correlation technique, the correlation coefficient = -0.372 with a significant level of p = 0.000 it is stated that there is a very significant negative relationship between fanaticism and verbal aggression in adolescents, the higher the sense of fanaticism, the lower the verbal aggression. in adolescents and vice versa, the lower the fanaticism, the higher the verbal aggression in adolescents Keywords: Fanaticism, Verbal Aggression